ANALYSIS OF THE EFFECTIVENESS OF PB DJARUM ADVERTISING SCHOLARSHIP USING THE EPIC METHOD IN 2020 - Abdul Muis, Muhammad; Juhari, Juhari; Rachmawati, Mila (Dinasti International Journal of Management Science, 2021)
This study aims to analyze about strategy effectivity of Empathy, Persuasion, Impact, and Communication (EPIC) PB Djarum. The used research methodology is a qualitative descriptive method with cross-section and primary data obtained from questionnaires, which is subsequently processed in the form of presentation of tables and charts. The used mechanical sampling is a purposive sampling method from data in 2020. The use of data analysis is using score calculation of EPIC method and calculation of effectivity level of it. The results of this study show that the variable Empathy score was 3.32 which is within the range of effective scale, variable Persuasion result of 3.26 is within the range of effective scale, variable Impact obtained a yield of 3.11 which is within the range of effective scale, Communication variables obtained results of 2.99 which is within the range of effective scale. These results indicate that strategy in the promotion of PB Djarum using EPIC method is effective as media promotion of PB Djarum. The overall value of empathy, persuasion, impact, communication on the EPIC rate is 3.17. It means the EPIC method is effective in promoting the films that will be shown at PB Djarum and can be used as one of the marketing tools.